If they don't care, I won't share: feeling unrelated to one's in-group increases selfishness instead of behavior for the greater good - Klein, Sina; Rudert, Selma C. (European journal of social psychology, 2021)
Individuals cooperate more with others to whom they feel connected. As a consequence, reduced belonging to an in-group decreases cooperation with this group, but not with others. Sometimes, however, there may be no new group available to (re)affiliate with. In this case, reduced belonging may either increase cooperation on a higher level, such as with the superordinate group humanity, or increase selfishness. We investigate this in an online experiment and a survey study. Study 1 (N = 299) showed that being ostracized in Cyberball reduced cooperation with the ostracizers and increased selfish behavior, while cooperation with humanity did not increase. Similarly, Study 2 (N = 1300) showed that lower feelings of belonging were associated with more selfishness, as fewer participants decided to donate to a humanitarian cause. These findings highlight the importance of inclusion and integration for societies and communities who wish to maintain a high level of cooperation.
Gesehen am 12.04.2023